Human Rights in Xinjiang 1978-2007: Internationalisation of the Uyghur Dilemma and China’s Reaction - Rogers, Roy Anthony (Journal of International Studies, 2020)
Since 1978 when Deng Xiaoping took over the leadership of China after the demise of Mao Zedong in 1976, the country witnessed dramatic changes in the human rights situation. These included freedom in performing religious obligations such as pilgrimage, for the Muslim Uyghurs and freedom to practice their culture and language. Hence, there was an overall improvement in human rights situation in Xinjiang province. However, in the late 1990s the Chinese Communist Party reverted to harsh policies once again. They declared the policy of ‘Strike Hard’ which sanctioned the use of torture and arbitrary detention as well as extra-judicial killings of the Uyghurs. This article examines the factors that have influenced China’s policies on the human rights condition in Xinjiang from 1978 until 2007. It also analyses the role of Uyghur diasporas in their struggle to internationalise the human rights issues in Xinjiang and China’s reaction towards the international pressures.